2019
DOI: 10.3389/fped.2019.00256
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in Children and Adults—What Are the Differences and What Can They Tell us About Asthma?

Abstract: Asthma varies considerably across the life course. Childhood asthma is known for its overall high prevalence with a male predominance prior to puberty, common remission, and rare mortality. Adult asthma is known for its female predominance, uncommon remission, and unusual mortality. Both childhood and adult asthma have variable presentations, which are described herein. Childhood asthma severity is associated with duration of asthma symptoms, medication use, lung function, low socioeconomic status, racial/ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
123
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(168 citation statements)
references
References 159 publications
9
123
2
1
Order By: Relevance
“…Asthma in early childhood differs from asthma in later childhood or adulthood. 16 Assessments of wheezing phenotypes in several cohorts have shown that some children may wheeze early in life and not later, whereas others may have either persistent wheeze or late-onset wheeze. 17 Thus, children who wheeze in early childhood may have remission of their symptoms by the time they reach school age.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma in early childhood differs from asthma in later childhood or adulthood. 16 Assessments of wheezing phenotypes in several cohorts have shown that some children may wheeze early in life and not later, whereas others may have either persistent wheeze or late-onset wheeze. 17 Thus, children who wheeze in early childhood may have remission of their symptoms by the time they reach school age.…”
Section: Discussionmentioning
confidence: 99%
“…The first one was divided into children and adults, considering that the incidence of adult asthma is more unstable, the recurrence rate is higher and the remission rate is lower than that of childhood asthma. [13] Another subgroup was classified according to the clinical stage of asthma. On acute attack of asthma, treatment should focus on rapid relief of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that patients current asthma had a significant elevated C-reactive protein concentration than those with former asthma or never asthma, but there was not significant difference in C-reactive protein concentration among those with former asthma and non-asthma which supported our finding that current asthma not former asthma was associated with increased CVD, chronic lower respiratory diseases and all-cause mortality 26 . Asthma was such a heterogenous disease, adult-onset and childhood-onset asthma appeared to run a different course and had different characteristics 33 . Childhood-onset asthma was mild and remission was common 33 .…”
Section: Discussionmentioning
confidence: 99%